Тренди ливарного ринку України в першій чверті XXI століття - Гнатуш, В. А.; Дорошенко, В. C.; Клименко, С. І. (Physico-technological Institute of Metals and Alloys, 2023)
An analysis of the state of foundry production in Ukraine is presented. The foundry industry of Ukraine in the 21st century significantly reduced its production indicators, which is due to the influence of such factors as the stagnation of industries that consume metal castings, as well as a decrease in exports. This situation has been negatively affected by the COVID-19 pandemic, as well as the global foundry industry, due to a decrease in demand for castings from end manufacturers. It was predicted that positive developments should be expected in the near future. However, russia's attack on Ukraine on February 24, 2022 made a significant correction in the development of the global economy, and, accordingly, in the functioning of the world foundry industry. Ukrainian companies in the foundry industry felt the impact of the war, some of them suffered partial destruction of their production premises. Large foundry enterprises of Ukraine are mostly located in the south-eastern regions, which were the most affected by hostilities. At the same time, in order to reflect the real situation in the foundry industry of Ukraine, it is advisable to organize the collection of real data regarding the production of castings from various alloys in the country, as well as regarding the export and import of foundry products. This will make it possible to make effective decisions regarding the program of modernization of the industry and the development of industries that consume domestic metal castings. Ultimately, this will help increase the competitiveness of Ukrainian products and increase revenues to the budget of Ukraine. To assess the direction of development of foundry production in advanced countries of the world, the statistical data of the leading countries regarding the production of castings and in more detail such countries as Poland, Germany and the USA are given. The structure of cast products produced in the world is in constant dynamics and there is a constant change in the ratio of the volumes of castings produced from various alloys. Recent years have been characterized by a tendency to reduce the production of castings from steel and gray iron with a simultaneous increase in the share of castings from highstrength cast iron and aluminum alloys.